A case of combined treatment of severe chronic thromboembolic pulmonary hypertension - R. S. Akchurin; I. E. Chazova; K. V. Mershin; T. V. Martynyuk; T. V. Vdovenko; N. M. Danilov (Медицинский совет, 2015)
Chronic thromboembolic pulmonary hypertension (CTEPH) is a rare disease which occurs in 1-3% of patients [2, 11] after pulmonary embolism. The incidence of CTEPH is 5-10 cases per 1 million population per year. Similar to other diseases associated with pulmonary hypertension (PH), CTEPH is malignant and has a poor prognosis. [4, 6, 8] There are a number of objective difficulties in the diagnosis of the disease: complaints and symptoms are very non-specific, there are often no X-ray aor ECG changes, echocardiographic signs of overload of right heart chambers are observed in the final stages of the disease. [9, 3] A strong inclination of doctors to primarily seek problems in the left heart chambers also plays a part in this. As a result, a patient may be visiting various specialists for years and receive treatment from different ailments including heart failure, asthma, pulmonary fibrosis, obstructive bronchitis. We had a case where a female patient with CTEPH received prednisolone for asthma for a long time while she had normal spirometry!